2009
DOI: 10.1364/oe.17.005373
|View full text |Cite
|
Sign up to set email alerts
|

Optically-pumped saturable absorber for fast switching between continuous-wave and passively mode-locked regimes of a Nd:YVO_4 laser

Abstract: Abstract:We report on the fast (~50 s) remote-controlled switching between continuous-wave (cw), cw mode-locked (ML) and Q-switched ML modes of operation of a Nd:YVO 4 laser using an optically-pumped saturable absorber (SA). Pulses as short as 40 ps with an average output power of 0.5 W are obtained in cw ML regime. Burns, "Thermal management in vertical-external-cavity surface-emitting lasers: Finite-element analysis of a heatspreader approach," IEEE J. Quantum Electron. 41, 148-155 (2005). 15.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…When the EDL was turned on with 1W of output power and its ~100μm-radius beam coincided with the Cr:LiSAF laser cavity mode on the SBR, the laser switched to CW ML operation. The physical processes behind this change of mode of operation were discussed in details in [2,3] where it was shown that the major factor responsible for switching is a fast heat-induced shift of the absorption edge of the SBR towards longer wavelengths resulting from the pumping of the SBR. Indeed, this localized heating induces laser mode switching with transient times orders of magnitude shorter than when the SBR is directly heated by a Peltier element [2][3][4].…”
Section: Experimental Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…When the EDL was turned on with 1W of output power and its ~100μm-radius beam coincided with the Cr:LiSAF laser cavity mode on the SBR, the laser switched to CW ML operation. The physical processes behind this change of mode of operation were discussed in details in [2,3] where it was shown that the major factor responsible for switching is a fast heat-induced shift of the absorption edge of the SBR towards longer wavelengths resulting from the pumping of the SBR. Indeed, this localized heating induces laser mode switching with transient times orders of magnitude shorter than when the SBR is directly heated by a Peltier element [2][3][4].…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Ultrafast pulsed solid-state lasers are becoming ubiquitous tools for an ever-increasing range of applications including scientific research, material processing and bio-photonics [1][2][3][4][5]. This use has widespread as they have gained in reliability, ease of operation and reduced maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…These switchable systems conveniently offer the functionality of two devices in one and are particularly useful in biological imaging 6 , cell manipulation and cell dissection 7 . For example, switching between CW and pulsating regimes has been obtained with mode-locked solid-state lasers with saturable absorber 8 and bragg reflector 9 , 10 sections. Whilst such systems can provide ultrashort pulses with very high energies, they typically require optical pumping operation, have large footprints, slow repetition rates and yield moderately long switching times (~μs timescales) between CW and pulsating regimes.…”
Section: Introductionmentioning
confidence: 99%
“…The work of Savitski et al [4] has shown that optical control of a SESAM through induced localized heating close to the control laser beam focus can be effective in altering the absorption spectrum of a quantum-well saturable absorber. They have also demonstrated the use of such lasers in optical trapping experiments where controlled two-photon responses can be achieved [5].…”
Section: Introductionmentioning
confidence: 99%